Estimating energy savings from behaviours using building performance simulations. Issue 3 (3rd April 2017) - Lopes, Marta A. R.; Antunes, Carlos Henggeler; Reis, Ana; Martins, Nelson
ABSTRACT: Occupants' behaviours are a major determinant of energy use in buildings. The related savings potential has been insufficiently exploited. Although research has addressed behavioural savings through real-world interventions and quantitative modelling approaches, it has not yet explored the full variety of household activities. This work proposes an integrative modelling approach of energy behaviours in the residential setting as a tool to estimate the behavioural impact of households on energy consumption. It uses building energy performance simulation (BEPS) tools to exploit the behavioural savings potential associated with usage and investment energy behaviours when using different energy services in daily household activities. Simulations have estimated significant behavioural savings potential associated with energy behaviours, which may be materialized if some forms of behaviour are induced. Investment behaviours have higher savings potential than usage behaviours, and the behavioural savings potential per energy service is proportional to the energy consumption breakdown. BEPS tools enable a quantitative estimate of the behavioural impact on energy consumption, but further improvements to these tools are needed to incorporate the complexity of behavioural dimensions. Estimating the behavioural savings potential is important for a more effective design of behaviour change interventions, which in turn will support more effective energy efficiency policies.